Production of anti-GM3, anti-GM1, and anti-GD1A antibodies by non-lymphoid cells, tissues, and organs - Iskra Sainova; Vera Kolyovska; Desislava Drenska; Dimitar Maslarov; Andrey Petrov; Dimitrina Dimitrova-Dikanarova; Tzvetanka Markova (Pensoft Publishers, 2024)
Gangliosides are acidic glycosphingolipids localized mainly on the outer membrane layer of the membranous cell structures. These molecules participate in important mechanisms at molecular, cellular, tissue, organ, and organism levels. It has been proven that gangliosides play a role as regulators of various biological processes but also as markers in a number of multifactor pathologies. In this regard, the present study determined the titers of the GM3, GM1, and GD1a gangliosides, as well as the titers of IgG-class antibodies against each of them by enzyme-linked immunosorbent assay (ELISA), in several different anatomic organs: brain, pancreas, myocardium, liver, and small intestine from rodents. A total extract (control sample) containing the complete set of molecules is prepared from each isolated anatomic organ. An equivalent amount of the extract is passed through a GSH-agarose column in order to select the molecules from each organ possessing affinity to the reduced form of glutathione tripeptide (GSH). GSH is known as an antioxidant, immunomodulator, cardioprotector, neuroprotector, hepatoprotector, anticancer, and antiaging agent. As a whole, significantly lower titers of the three gangliosides and the antibodies to them are reported in the myocardium and liver samples compared to the brain and pancreas samples. Taking into account that the myocardium and liver are the organs known with the highest content of GSH, the obtained results can be explained by the possibly high content of free and/or newly synthesized GSH in them, which does not participate in intermolecular interactions compared to the other investigated organs. Complete absence of each of the three tested gangliosides or of antibodies against them at certain dilutions of the small intestine samples, as well as the highest titers of the same parameters compared to the corresponding samples from the other organs of each of the gangliosides or of the specific antibodies at other dilutions, is observed. One of the explanations for those peculiarities is associated with the presence of the intestinal microflora, including the influence of intestinal bacteria neuraminidases (sialidases). The presented data also show a possibility of antibodies/immunoglobulins production by non-lymphoid cells, tissues, and organs in suitable conditions. Since the immunoglobulins thus produced reside outside the germinal centers of the specialized lymphoid tissues and organs, regulation of their production and functions by interactions with small ions and/or molecules is also important. Gangliosides are namely such small molecules. Special attention is paid to intermolecular interactions involving the listed gangliosides and GSH. The main objective is related to understanding the mechanisms underlying the interaction between the individual organs and systems in the body.